The influence of porosity on radon emanation in alkali-activated mortars containing high volume bauxite residue. (10th January 2020) - Gijbels, Katrijn; Krivenko, Pavel; Kovalchuk, Oleksandr; Pasko, Anton; Schreurs, Sonja; Pontikes, Yiannis; Schroeyers, Wouter
Highlights: Dissolvement of bauxite residue upon alkali activation increases emanation. Mesopore size distribution strongly determined by the production process followed. Higher cumulative mesopore volume results generally in higher emanation rates. Low correlation between specific surface area and emanation. Abstract: In this study the influence of porosity on radon emanation was examined when incorporating high volume bauxite residue, ranging from 30 to 90 wt%, in alkali-activated mortars. Samples were produced using the semi-dry pressing and the high-slump-casting techniques. The porosity and specific surface area were assessed by means of N2 adsorption/desorption. Upon alkali activation, part of the bauxite residue dissolved, increasing the emanation coefficient. The mesopore size distribution was strongly determined by the process followed, and higher cumulative mesopore volumes resulted generally in higher emanation rates. Low correlation was found between the specific surface area and emanation coefficient.